1996
DOI: 10.1007/bf01533190
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in pathological gamblers seeking treatment

Abstract: High rates of psychiatric symptoms have been reported in pathological gamblers. This study of psychiatric comorbidity in pathological gamblers is the first to use structured psychiatric interviews assessing DSM-III-R Axis I and II disorders. The Structured Clinical Interview for DSM III-R (SCID-P, SCID-II) was administered to 40 (25 male, 15 male) pathological gamblers seeking outpatient treatment in Minnesota for gambling, and 64 (41 male, 23 female) controls. High lifetime rates of Axis I (92%) but not Axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
1
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(102 citation statements)
references
References 25 publications
10
82
1
9
Order By: Relevance
“…First, higher rates of internalizing/affective disorders push women towards non-social games like video lottery terminals (VLTs) (Boughton & Falenchuk, 2007;Grant et al, 2002). Second, the monotony and minimal effort required by VLTs provide an easy and desired dissociative effect in the face of stress and negative emotions (Ibanez et al, 2003;Specker et al, 1996). Third and finally, women who hold lower (real or perceived) status prefer "equal/random chance" games because they can participate on equal terms to the person next to them, regardless of social status or demographics (Bunkle, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, higher rates of internalizing/affective disorders push women towards non-social games like video lottery terminals (VLTs) (Boughton & Falenchuk, 2007;Grant et al, 2002). Second, the monotony and minimal effort required by VLTs provide an easy and desired dissociative effect in the face of stress and negative emotions (Ibanez et al, 2003;Specker et al, 1996). Third and finally, women who hold lower (real or perceived) status prefer "equal/random chance" games because they can participate on equal terms to the person next to them, regardless of social status or demographics (Bunkle, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Often, they experience instability or trauma during childhood, abusive or troublesome relationships in adulthood, and low (real or perceived) social status (Boughton & Falenchuk, 2007;Bunkle, 2009;Petry & Steinberg, 2005;Specker, Carlson, Edmonson, Johnson & Marcotte, 1996). As a result, another reason women often turn to gambling is for a temporary sense of empowerment (Bunkle, 2009;Casey, 2008).…”
Section: Describing Gender Differences Among Problem Gamblersmentioning
confidence: 99%
“…Earlier research has also reported high percentages of the Cluster A and Cluster C disorders among treatment seeking gamblers (Steel & Blaszczynski, 1998). Various researchers have identified a relationship between Cluster C diagnoses and PGD in treatment samples (Specker et al, 1996;Steel et al, 1998), particularly for Avoidant Personality (Specker et al, 1996) and Obsessive-Compulsive Personality Disorder (Black & Moyer, 1998). For example, in a study of psychiatric outpatients, Henderson (2004) found that those with PGD displayed elevated scores on Avoidant, Compulsive, and Self-Defeating Personality Scales.…”
Section: Pathological Gambling and Personality Disordersmentioning
confidence: 99%
“…Similarly, treatment studies have also demonstrated an association between ASPD and gambling, showing ASPD rates of 14.5% (Ibanez et al, 2001) to 16.5% (Pietrzak & Petry, 2005). However, one study of PGD treatment seekers contradicted the ASPD connection in that it failed to identify any individuals with ASPD; their findings were potentially a result of methodological issues related to sample size, regional variation, and high levels of education (Specker et al, 1996).…”
Section: Pathological Gambling and Personality Disordersmentioning
confidence: 99%
“…The Productivity Commission 1 identified a number of characteristics shared by people experiencing gambling problems: Research has identified the extent of psychiatric comorbidity with pathological gambling [4][5][6] , and to a lesser extent other health concerns 7 . DeCaria et al 4 found that among an outpatient sample of pathological gamblers 28% met criteria for major depressive disorder, 24% bipolar disorder and 28% anxiety disorders.…”
Section: Abstract Problem Gambling Comorbidity Screening Tools Eamentioning
confidence: 99%